Naringenin reduces early brain injury in subarachnoid hemorrhage (SAH) mice: The role of the AMPK/SIRT3 signaling pathway. (September 2020) - Zeng, Hanhai; Shao, Bo; Zhuang, Jianfeng; Peng, Yucong; Chen, Huaijun; Yu, Qian; Xu, Chaoran; Fu, Xiongjie; Zhou, Hang; Cao, Yang; Yu, Xiaobo; Li, Jianru; et al.
Graphical abstract: Highlights: Naringenin improved neurological function and alleviated brain edema after SAH. Naringenin attenuate neuroinflammation after SAH. Naringenin attenuated cell apoptosis after SAH. AMPK/SIRT3 signaling pathway may be the underlying mechanisms. Abstract: Naringenin exhibits multiple pharmaceutical effects, while the effects of naringenin on early brain injury (EBI) after subarachnoid hemorrhage (SAH) and its underlying mechanism have not been well-studied yet. Here, male C57BL/6 mice were utilized to the endovascular perforation model of SAH. Naringenin, 3-TYP (a selective SIRT3 inhibitor), Compound C (an AMPK inhibitor) were administered. Naringenin can attenuated neurological deficits and cerebral edema after SAH. Besides, naringenin reduced the number of Iba-1-positive and apoptotic cells. Moreover, naringenin decreased the expression of inflammatory cytokines. And naringenin upregulated the expression of phosphorylated AMPK (pAMPK) and SIRT3, which were abolished in mice with combined administration of naringenin and Compound C. However, administration of naringenin combined with 3-TYP did not enhance the expression of pAMPK, implying that AMPK is an upstream protein of SIRT3 in SAH under naringenin treatment. In summary, naringenin attenuated neuroinflammation and apoptosis after SAH. The potential mechanisms involved AMPK/SIRT3 signaling pathway.